Child-led research, children's rights and childhood studies: A defence. (May 2021) - Thomas, Nigel Patrick
Recent articles by Kim and Hammersley have critiqued, respectively: the methodological and normative assumptions that underlie research 'by' children; claims made about the implications of children's rights for the ethics of research with children; and more broadly, some of the central commitments of Childhood Studies. This paper offers a response to these critiques, seeking to distinguish between those that clearly should be accepted, those that appear to be based on a misreading of the claims being made by scholars and researchers, and those that represent serious challenges to defend, redefine or rethink our aims, claims or practices.